Long-Term Trends in the Attractiveness of Obstetrics and Gynecology Among Spanish Medical Graduates: Evidence from the MIR Allocation System (2001–2026). - Sánchez-Romero, Javier; Alfaro-Martínez, José Joaquín; Rovira-Negre, Ramón; Cánovas-López, Laura; San Frutos-Llorente, Luis Manuel; Oliva-Sánchez, Raquel (Spanish Journal of Medical Education, 2026)
Objective: To analyze the evolution of the attractiveness of OBGYN within the Spanish Medical Residency Training System (MIR) between 2001 and 2026 using objective indicators of specialty choice. Methods: A retrospective observational study was conducted using publicly available data from the Spanish Ministry of Health. Annual OBGYN residency allocation data from 2001 to 2026 were analyzed. Indicators included the number of positions offered, first and last rank numbers selecting the specialty, median rank number, demand rankings, and quotation index. Temporal trends were evaluated using descriptive analyses and graphical representations. Results: During the study period, the number of OBGYN residency positions increased from 181 to 284 (+56.9%). The rank number of the last allocated position increased from 2,578 to 4,521, whereas the quotation index remained relatively stable, ranging from 113.5 to 139.1. OBGYN consistently occupied a favorable position among MIR specialties, ranking between 10th and 17th place in the global quotation ranking and between 2nd and 6th place among medical-surgical specialties. Top-demand and total-demand indicators also remained consistently favorable, with OBGYN generally positioned among the most demanded specialties throughout the study period. Conclusions: Despite substantial changes in healthcare systems, professional expectations, and working conditions, the attractiveness of OBGYN within the Spanish MIR system remained stable over the last 26 years. Although some rank-based indicators worsened over time, demand- and quotation-based measures continued to position OBGYN among the most attractive medical and surgical specialties. These findings do not support the widespread perception of a progressive decline in the attractiveness of the specialty.